2009
DOI: 10.1166/jnn.2009.c063
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectric Characteristics of Natural Pigments Self-Assembly Fabricated on TiO<SUB>2</SUB>/FTO Substrate

Abstract: Natural pigment can act as an inexpensive and biologically-friendly dye, which is fabricated on a TiO2/FTO substrate. Natural pigments promote the efficiency of the photoelectric conversion in water-based DSSC with the aqueous electrolyte of the Ce+4/+3 system. The open-circuit voltage (Voc) of natural pigment in water-based DSSC is 0.640 V. The short-circuit current (Isc) of natural pigment in water-based DSSC is 0.658 mA/cm2. The efficiency of the photoelectric conversion in water-based DSSC of natural pigme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The absorption spectra of 50 g/L of natural pigments in alcohol are presented in Figure 5. The absorption peaks at 465 and 665 nm result from the Soret band (B) and Q band absorption of chlorophyll a, respectively [25][26][27][28][29]. The green part of Codiaeum varie, red part of Aglaonema, and green part of Aglaonema are rich in chlorophyll a.…”
Section: Photoelectric Characteristics Of Natural Pigments Deposited mentioning
confidence: 99%
“…The absorption spectra of 50 g/L of natural pigments in alcohol are presented in Figure 5. The absorption peaks at 465 and 665 nm result from the Soret band (B) and Q band absorption of chlorophyll a, respectively [25][26][27][28][29]. The green part of Codiaeum varie, red part of Aglaonema, and green part of Aglaonema are rich in chlorophyll a.…”
Section: Photoelectric Characteristics Of Natural Pigments Deposited mentioning
confidence: 99%
“…On the other hand, dye aggregation can be beneficial to solar energy conversion in that it is often accompanied by spectral broadening which can improve the overlap of the device optical absorption with the solar spectrum. Structured biomimetic chromophore assemblies are being pursued with the goal of exploiting energy transfer in solar energy conversion, and there is additional incentive to replace costly synthetic sensitizers with natural pigments. Unfortunately, none of these biomimetic approaches have resulted in energy conversion efficiencies that rival those of DSSCs using monomeric organic or metallorganic sensitizers. Better understanding of the influence of aggregation on TiO 2 -based solar energy conversion should permit the enhanced light harvesting of dye assemblies to be exploited without diminished yield of photoelectrical conversion.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that extremely low oxygen and sulfur concentrations in steel can be achieved via the addition of an RE metal14. A lot of research15161718 has also been done on steel deoxidization and desulfurization via titanium and magnesium. RE metals can be used to deoxidize and desulfurize steel to control inclusion size and chemical composition.…”
mentioning
confidence: 99%